Comics : easy as ABC! : the essential guide to comics for kids : for kids, parents, teachers and librarians! - Brunetti, Ivan (TOON Graphics., 2019)
"Cartoonist Ivan Brunetti teams up with editor Françoise Mouly to create a comprehensive Comics how-to booklet, geared towards parents, teachers, librarian, and children alike"--